Microbiological profile of antimicrobial sensitivity and resistance in a general hospital in the Peruvian jungle 2021: Perfil microbiológico de sensibilidad y resistencia antimicrobiana en un hospital general de la selva peruana 2021 - Amado, Jose (2024)
Introduction: Antimicrobial resistance increases hospital mortality and is a public health problem. Objective: to determine the characteristics of microorganisms isolated from hospitalized patients and to detail antimicrobial sensitivity profiles. Methodology: cross-sectional study Cross-sectional study in a hospital in the Peruvian jungle during 2021. The type of microorganism, antimicrobial sensitivity (VITEK ® 2 bioMérieux), source of isolation, patient age and hospitalization service were identified. Results: 477 positive cultures were included in 453 patients. The samples came from bronchial secretion 54.9%, blood 35.2%, urine 6.5% and others 3.4%. The hospital services of origin were emergency 49.9%, intensive care unit 40.0%, medicine 9.6% and surgery 0.5%. Gram negative bacteria (74.6%), Gram positive bacteria (16.4%) and fungi (9%) were isolated. The most frequently isolated microorganisms were Acinetobacter baumannii complex (32.7%), Klebsiella pneumoniae ssp. (16.8%) and Pseudomonas aeruginosa (13.4%). Antimicrobial resistance for the most frequently isolated microorganisms was: Acinetobacter baumannii complex, XDR in 88.5%; Klebsiella pneumoniae ssp., MDR in 56.3%; Pseudomonas aeruginosa, XDR in 54.7%; Staphylococcus epidermidis, MDR in 92.3%; and Staphylococcus haemolyticus, MDR in 100%. Conclusions: Gram-negative bacteria are the most prevalent, being more affected hospital critical areas, finding a high percentage of antimicrobial resistance.